Revista Visão: construção, organização e difusão do projeto neoliberal no Brasil na década de 1970 - Cezar Junior, Gervasio (2012)
This paper has analysed the supporting action from the extinct Visão magazine, as well as the participation of its main intelectual and owner Henry Maksoud, during the years from 1974 to 1979. The respected period is part of the civil-military dictatorship process estabilished in Brazil from the 1964 coup, more precisely, the 1970s were characterised by a radical change regarding the way of leading the economy, most of all by the advent of the II PND ( II Plano Nacional de Desenvolvimento). In order to understand the role played by Visão in the society, we have based ourselves on the frame produced by the revolucionary Italian philosopher Antonio Gramsci, to be more specific on his considerations around the conception of the private apparatus of hegemony. The first chapter of this dissertation has in itself the base of the theorical discussion used in all the paper. And more, he relies on the the last topic where we discussed the historical trajectory of the building of the neoliberal project. Through the chapter two, we have showed in which instances the relationship between Visão and ABDIB was given, sustained and shaken, mainly, by the creation of the II PND. The third chapter has as its main goal to expose the intimate relationship between Visão and the Anti Natonalize Campaign, showing how Visão supported itself on the Anti Natonalize Campaign in order to begin the dissemination of the neoliberalism in Brazil. On the chapter four we have showed which classical intelectuals from neoliberalism, as well as their main thesis, are used by Visão to help on the improvement and organization of the Brazilian neoliberal program. Thus we have identified that Visão acts while an organizing agent from the neoliberal Project for Brazil, already in the 1970 decade, mainly supported on Frederick August von Hayek premises, principally mediated by Henry Maksoud, owner and editor chief of the magazine.